Advertising and Ethical Theories – A Comparative Study of Select Campaigns (International Journal of Scientific Research and Management (IJSRM), 2015)
In business it is an accepted fact that the purpose of business is to make profits. At functional level the decisions are about what is right and wrong. Marketing and advertising both reflect and shape cultural values and norms. Through this paper an attempt is made to understand if there is any ethical dimension in the advertising or marketing communication. Some select advertisements of TV and print are taken as sample for study from the different ethical perspectives. The authors have taken the liberty of adding their views on the same. The paper highlights that there is no ethical norm followed by marketer other than the profit motive. While the paper also acknowledges that the job of marketing promotion is to sell the product and strict guidelines or law would drive the creativity away from advertising and promotion. But allowing a free run would harm the consumers, competitors, and society. The authors believe that an ethical framework and a very tight control and monitoring mechanism for unethical marketing promotion are the key to success in Indian situation.